KARAKTERISTIK ORGAN SEKSUAL SEKUNDER IKAN TUDE BATU (SELAR BOOPS) DARI PERAIRAN BITUNG - Rudi Saranga; Muhammad Zainul Arifin; Fitroh Dwi Hariyoto; Elsari Tanjung Putri; Achmad Jais Ely (JURNAL BLUEFIN FISHERIES, 2021)
Selar boops is a group of small pelagic fish in the Carangidae family, this fish is known by the Bitung people as Tude Batu. This fish has economic value which is caught by fishermen in the waters around Bitung City using hand line fishing. This study aims to identify the secondary sexual organs. Fish samples were collected from 2 locations, namely Kampung Pisang and Pasar Winenet. The secondary sexual organs are identified by observing the morphological using the morphometric truss method of 19 morphological characters. Anova K-Means Cluster (AKMC) analysis as well as discriminant analysis were used to differentiate male and female fish groups. The results of this research showed that the morphometric characteristics of secondary sexual organs in male and female S. boops. The results showed that there were 11 different morphometric truss for morphometric characters in secondary sexual organs of male and female S. boops using AMKC analysis. The results of the discriminant analysis showed that the characteristics of the secondary sex organs in S. boops fish were found in the ratio of pectoral fin length (PaSiPek) and head length (PaKe) with a discriminant value (D) <0 grouped as male fish and discriminant value (D)> 0 classified as female. Keywords : discriminant, morphometry, secondary sexual organs, tude batu